Pengaruh Strategi Active Learning Tipe Turnamen terhadap Hasil Belajar Volume Bangun Ruang di Sekolah Dasar - Sonia Loliza; Risda Amini (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research aims to find out what the effect of using the tournament type active learning strategy on learning outcomes of the volume building in the fifth grade elementary school. The method used in this research is a quasi-experimental research design with nonequivalent control group design. The population of this research was all students of the fifth grade elementary school cluster IV, East Padang District, West Sumatera. The technique of collected data was simple random sampling, so elementary school 20 Air Camar was selected as the experiment class and elementary school 17 Parak Karakah as the control class. The instrument of the research was an essay test. The data analysis technique used the t-test. Based on the results of data analysis from hypothesis testing using t-test obtained tcount = 3.60 while ttable at a significant level of 0.05 and dk = 40 is 2.021, so H1 was accepted because tcount > ttable. Thus, there is a significant effect on the type of tournament active learning strategy on learning outcomes of the volume building in the fifth grade elementary school.